Cluster of Mycobacterium smegmatis mastitis cases in a dairy herd incorporating recycled manure solids bedding - Lindeberg, Heli; Seppänen, Jaana; Frondelius, Lilli; Pohjanvirta, Tarja; Autio, Tiina (Frontiers in Veterinary Science, 2026)
This study examined uncommon mastitis cases in a research barn incorporating recycled manure solids (RMS) as bedding. The cases occurred after barn renovation, including the conversion of the herringbone milking parlor to an automatic milking system (AMS) and the replacement of rubber mattress stalls with deep-bedded stalls maintained daily with RMS. Cows were milked at the herringbone milking parlor until the automatic milking system was available. Approximately 6 months after the implementation of AMS and deep-bedded stalls, the first two cows exhibited cow level somatic cell counts ≥ million cells/ml and palpable hardness in udder quarters manifested. However, commercial quantitative polymerase chain reaction testing, typically employed for mastitis diagnostics in Finland, did not identify pathogens in the quarter milk samples. Mycobacterium smegmatis was isolated through bacterial culturing. Within 9 months, five more M. smegmatis mastitis cases occurred in the dairy barn. Whole genome sequencing (WGS) of the isolates revealed considerable genetic diversity among strains. However, chronic infections in individual quarters caused by persistent strains were also detected. The WGS-based core-genome multilocus sequence typing approach demonstrated its efficacy as a robust tool for the molecular epidemiological exploration of bovine non-tuberculous mycobacterial mastitis. All lactating cows were tested for Mycobacterium avium subspecies paratuberculosis antibodies using an enzyme-linked immunosorbent assay test. Only the cows with M. smegmatis mastitis gave a positive reaction, although the causative agent of paratuberculosis was not detected in their fecal samples.